Suramin analogues protect cartilage against osteoarthritic breakdown by increasing levels of tissue inhibitor of metalloproteinases 3 (TIMP-3) in the tissue - Green, Jonathan; Tinson, Ryan A.J.; Betts, Jacob H.J.; Piras, Monica; Pelut, Aylin; Steverding, Dietmar; Wren, Stephen P.; Searcey, Mark; Troeberg, Linda (Bioorganic & medicinal chemistry, 2023)
[Display omitted] Osteoarthritis is a chronic degenerative joint disease affecting millions of people worldwide, with no disease-modifying drugs currently available to treat the disease. Tissue inhibitor of metalloproteinases 3 (TIMP-3) is a potential therapeutic target in osteoarthritis because of its ability to inhibit the catabolic metalloproteinases that drive joint damage by degrading the cartilage extracellular matrix. We previously found that suramin inhibits cartilage degradation through its ability to block endocytosis and intracellular degradation of TIMP-3 by low-density lipoprotein receptor-related protein 1 (LRP1), and analysis of commercially available suramin analogues indicated the importance of the 1,3,5-trisulfonic acid substitutions on the terminal naphthalene rings for this activity. Here we describe synthesis and structure–activity relationship analysis of additional suramin analogues using ex vivo models of TIMP-3 trafficking and cartilage degradation. This showed that 1,3,6-trisulfonic acid substitution of the terminal naphthalene rings was also effective, and that the protective activity of suramin analogues depended on the presence of a rigid phenyl-containing central region, with para/para substitution of these phenyl rings being most favourable. Truncated analogues lost protective activity. The physicochemical characteristics of suramin and its analogues indicate that approaches such as intra-articular injection would be required to develop them for therapeutic use.